An application of the decomposition method for second order wave equations - Kaya, D (Gordon Breach Sci Publ Ltd, 2000)
In this paper we study the solution of a linear and nonlinear damped wave and dissipative wave equations by Adomian decomposition method. We illustrate that the analytic solutions and a reliable numerical approximation of the damped wave and dissipative wave equations are calculated in the form of a series with easily computable components. The nonhomogeneous problem is quickly solved by observing the self-canceling noise terms whose sum vanishes in the limit. In comparison to traditional techniques, the series based technique of Adomian decomposition method is shown to evaluate solutions accurately and cheaply.
Keywords: the decomposition method; a linear damped wave equation; a nonlinear damped wave equation; a dissipative wave equation; the self-canceling noise terms